Досвід організації просторів з фонтанами у населених пунктах України (Частина 1) - Церковна, Оксана Георгіївна; Вороніна, Анна Олександрівна (Теорія та практика дизайну, 2021)
Among the countries of Europe, Ukraine is marked by a fairly large number of the fountains, which are the pieces of the monumental art, cultural and historical heritage objects. The purpose of this publication: to summarize the experience of organizing spaces with fountains, to explore the development of fountains as artistic and aesthetic objects of urban and landscape architecture. The fountains are considered as an integral part of the historical and architectural heritage of the country’s settlements, which is associated with outstanding historical events and the lives of famous people. Having traced the historical preconditions for the appearance of spaces with fountains, еxplored the circumstances that contributed to the development of sciences in Ukraine and the emergence of the first fountains as a synthesis of art and engineering, elements of a centralized water supply system of the settlement. Traced the influence of political, economic and ecological circumstances and the cultural needs of society for changes in the organization of spaces with fountains, where the buildings transformed their original functions from water distributors that meet drinking, household and religious needs into objects of improvement, artistic and aesthetic elements of urban architecture and pieces of garden art, artistic and aesthetic elements of landscape architecture, were studied. This publication presents the first part of the study, which covers the period of XVIII - XIX centuries. Серед країн Європи — Україна відзначається досить великою кількістю фонтанів. які є об’єктами монументального мистецтва, пам’ятками культурної та історичної спадщини. Мета даної публікації: узагальнити досвід організації просторів з фонтанами, дослідити розвиток фонтанів як художньо-естетичних об’єктів міської і ландшафтної архітектури. Фонтани розглядаються як невід’ємна складова історико-архітектурної спадщини населених пунктів країни, що пов’язана з видатними історичними подіями та життям відомих людей. Простеживши історичні передумови появи просторів з фонтанами, розглянуті обставини, які сприяли розвитку наук на Україні і появі перших фонтанів — як синтезу мистецтва і інженерії, елементів централізованої системи водопостачання населеного пункту. Досліджено вплив політичних, економічних і екологічних обставин і культурних потреб суспільства на зміни в організації просторів з фонтанами, де споруди — з розподільників води, які задовольняли питні, побутові та релігійні потреби — змінив початкові функції, трансформуються у об’єкти благоустрою, художньо-естетичні елементи міської архітектури і твори садово-паркового мистецтва, художньо естетичних елементи ландшафтної архітектури. У даній публікації представлена ​​перша частина дослідження, яка охоплює період ХVIII - XIX ст.